If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (24 + 8x + 7y) + -1(4x + 6y + 56) = 0 Remove parenthesis around (24 + 8x + 7y) 24 + 8x + 7y + -1(4x + 6y + 56) = 0 Reorder the terms: 24 + 8x + 7y + -1(56 + 4x + 6y) = 0 24 + 8x + 7y + (56 * -1 + 4x * -1 + 6y * -1) = 0 24 + 8x + 7y + (-56 + -4x + -6y) = 0 Reorder the terms: 24 + -56 + 8x + -4x + 7y + -6y = 0 Combine like terms: 24 + -56 = -32 -32 + 8x + -4x + 7y + -6y = 0 Combine like terms: 8x + -4x = 4x -32 + 4x + 7y + -6y = 0 Combine like terms: 7y + -6y = 1y -32 + 4x + 1y = 0 Solving -32 + 4x + 1y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 4x + 32 + 1y = 0 + 32 Reorder the terms: -32 + 32 + 4x + 1y = 0 + 32 Combine like terms: -32 + 32 = 0 0 + 4x + 1y = 0 + 32 4x + 1y = 0 + 32 Combine like terms: 0 + 32 = 32 4x + 1y = 32 Add '-1y' to each side of the equation. 4x + 1y + -1y = 32 + -1y Combine like terms: 1y + -1y = 0 4x + 0 = 32 + -1y 4x = 32 + -1y Divide each side by '4'. x = 8 + -0.25y Simplifying x = 8 + -0.25y
| (7x-12)=(6y+8) | | 3t-2=10 | | 20r+15=365 | | (7x-12)-(-2x+3)= | | X^2+10x+C=-5+c | | 2500-40.5x=-3000 | | x-8=x-36 | | 15p+5=95 | | 9k+30=120 | | 10p+1=81 | | 2c+2=16 | | -2500-40.5x=-3000 | | 12+(-2)+7+4+(-6)= | | a=q^2+13q+23 | | 4y-2+y+29=6y+30-4y | | x-10=x-10 | | 7x+7x=48 | | (3x-15)-(-7x+4)= | | (2x+1)(2x)= | | 7(-3x+5)-1+-2-15x= | | 9(t^2)-6t+50=0 | | 5x+14=-14-9 | | -5y+8=-7 | | 8+2x-4=9x+7-4x | | N-5-7n=19 | | 0=15x+10 | | 38-2x=14-8x | | 7ln(8x+1)=13 | | 6y+7=43 | | -7x+5=-7x-7 | | -2500-40.5=-3000 | | h^3+2h^2-8h=0 |